2017
DOI: 10.1097/cej.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between X-ray repair cross-complementing group 1 gene polymorphisms and the susceptibility to colorectal cancer in a Malaysian cohort

Abstract: X-ray repair cross-complementing group 1 (XRCC1) is one of the key components in the base excision repair pathway that repairs erroneous DNA lesions and removes nonbulky base adducts for the maintenance of genome integrity. Studies have revealed that differences in individual DNA repair capacity can impact the interindividual variation in cancer susceptibility, tumour aggressiveness and treatment response. The relationship between XRCC1 and sporadic colorectal cancer (CRC) susceptibility, which is hitherto inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Many studies have indicated that XRCC1 expression is up-regulated in tumor progression and might be a risk factor for tumor progression [ 8 , 11 ]. However, a recent publication showed a lack of correlation between XRCC1 gene polymorphisms and colorectal cancer susceptibility in a Malaysian cohort [ 12 ]. In addition, it has been verified that XRCC1 has a low expression level in many kinds of cancers, and XRCC1 has been proposed to serve as an anti-cancer marker for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that XRCC1 expression is up-regulated in tumor progression and might be a risk factor for tumor progression [ 8 , 11 ]. However, a recent publication showed a lack of correlation between XRCC1 gene polymorphisms and colorectal cancer susceptibility in a Malaysian cohort [ 12 ]. In addition, it has been verified that XRCC1 has a low expression level in many kinds of cancers, and XRCC1 has been proposed to serve as an anti-cancer marker for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the R194W polymorphism, like us, most studies showed no association with CRC, namely, Han Chinese [ 13 ], Japanese [ 14 ], Norwegian [ 20 ], Polish [ 22 ], Italian [ 25 ], Mexican [ 29 ], and Malaysian [ 34 ]. However, some Asian studies reported a risk of CRC in carriers of the 194T allele, specifically in Han Chinese (OR = 1.30 (1.04–1.64), P =0.023) [ 8 ], Northeast Chinese (OR = 1.29 (1.07–1.55), P =0.007) [ 32 ], Korean (OR = 2.87 (2.01–4.11), P < 0.0001) [ 9 ], and Iranian (OR = 4.95, (2.11–11.6), P < 0.001) [ 35 ] ( Table 3 ).…”
Section: Discussionmentioning
confidence: 92%
“…It interacts with PARP1, OGG1, and APE1 to facilitate the BER processes. 29 Among its more than 300 poly- 18,41 These amino acid substitutions influence the protein-protein interactions between XRCC1 and other BER proteins resulting in altered efficiency, function, and damaged DNA repair capacity leading to genetic instability and carcinogenesis. 13,27,28,31,40,44 Findings regarding the associations of XRCC1 Arg399Gln with CRC have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…It has been associated with CRC among the Kashmiri population 38 , South Koreans 27 , Han Chinese from Jiangsu Province, East China 45 , Japanese 39 , and southwest Iranians. 40 However, lack of association has been noted in a Malaysian cohort 41 , Han Chinese from the southwest region of China 33 , and Mexican patients. 15 The difference in results from the Han Chinese population from two different parts of China has been reported due to differences in the study participants' geographical location and genetic makeup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation